Epidemiological study and potential of late PCR for diagnosis of schistosomiasis in North Western region of Nigeria - Mohammed, Kabiru (2015)
Background: Schistosomiasis is considered the most common and widespread parasitic infection with significant socio-economic and public health concern worldwide and continues to be a significant cause of morbidity and mortality in developing and underdeveloped countries, including Nigeria. Objectives: This study aimed to determine the prevalence and risk factors associated with infections by S. haematobium and S. mansoni in three states of North-western Nigeria, and to develop and evaluate Linear-After-The-Exponential- Polymerase Chain Reaction (LATE-PCR) LFA for the detection of S. haematobium and S. mansoni in urine and stool samples. The latter was performed to establish and enhance accurate diagnosis of Schistosomiasis infection. Materials and Methods: Conducted in two phases. The first phase of the study was a cross-sectional survey, conducted between September, 2011 to September, 2012. Participants were selected based on simple random sampling. Structured questionnaire was used to assess socio-demographic information, and other associated determinant factors of the participants. Stool samples were examined using microscopy and formol ether concentration techniques while urine samples were examined using Filtration concentration techniques. Data were entered and analyzed using SPSS version 22.0 statistical software. Simple and multiple logistic regressions and chisquare test were used to explore the relationships between associated risk factors. Statistical significant was taken at the 5% level. The second part of the study involved development of LATE-PCR dipstick method to establish and enhance accurate diagnosis of S. haematobium and S. mansoni infection .Primers and probes targeting for, were designed for the two species specific amplification. The LATE-PCR LFA parameters were optimized and detection of PCR products was performed on 2% agarose gel electrophoresis, the nitrocellulose membrane was coated with biotinylated anti-mouse IgG (control line), anti-FITC (target line) and assembled as lateral flow strips. Results: Based on the 2451 participants, the study showed an overall prevalence of infection with S. haematobium to be 61.2% while the prevalence with Schistosoma mansoni parasites was 54.7%. The majority of the respondents were males (85.5%). Among the school children the highest prevalence of infection was detected in the 10-14 years (68.4% ). In Univariable analysis, children who belonged to low income household were 1.43 times highest odds of being infected with S. haematobium [ COR: 95% CI, 1.02, 2.00) p-value 0.042) as compared to those belonging to household families with monthly income of >USD 500. S. mansoni showed no significant association between income and risk of infection. Other factors that were found to be associated with S. haematobium infection in univariate analysis includes marital status whereby being single had more odds of getting infection compared to married respondents with (COR 1.97 (95% CI, 1.41:2.76; P=0.001). In final established multivariate analysis model, risk factors that remain significantly associated with Schistosomiasis infection include age group, snail contact, rented house, pit latrine system, Open space toilet and hands contact with water from the river. For S.haematobium infection risk factors were age group 5-17 (AOR,2.10 :95% CI,1.29,2.06,P=0.001), 18-29 years (AOR,1.37;95% CI: 1.08,1.74, P=0.007), Snail contact (AOR: 1.34,95% CI: 1.07,1.67,P=0.009), Rental house (AOR,1.61, 95% CI: 1.17,2.19: P=0.001), while for S. mansoni the main risk factors in the final established multivariable analysis model were Snail contact (AOR,1.44,95% CI:1.09,1.70, P=0.006), Pit system (AOR,0.68,95% CI:0.56,0.84,P=0.001) and lastly open space defaecation (AOR: 1.26, 95% CI: 1.06,1.51,P=0.009). The study findings revealed that age group, snail contact and defeacating in an open space was some of the major determinant risk factors for both species of schistosomiasis, it was thus therefore recommended that policy decision makers should intensify effort towards creating awareness through health education for prevention and control. The LATE-PCR LFA detected schistosoma DNA as low as 1 fg/μl of parasite DNA in urine and 1 ng/μl of DNA in stool samples.. The amplification reaction showed to be specific without any cross reaction with DNA from other intestinal microorganism Conclusion: The prevalence of schistosomiasis recorded in this study was extremely high and requires effective control and management strategies. Adult age group exposed to fishing and farming occupation, crossing river bare footed, snail contact, and rented house are some of predisposing factors identified for S. haematobium and S. mansoni infection in North-western, Nigeria. LATE-PCR LFA developed in this study provides a valuable alternative for the detection of S. haematobium and S. mansoni infection in the study area to speed up diagnosis in addition to the conventional method currently used.